Union of the Comoros : First Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for a Modification of Performance Criteria and Financing Assurances Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Union of the Comoros. (IMF Staff Country Reports; Country Report ;, 2010)
Recent developments in the Comoros point to slow, uneven, yet significant progress in political normalization. Overall performance under the Extended Credit Facility-supported program has been broadly satisfactory. The government understands the need to continue fiscal consolidation in support of macroeconomic objectives, targeting a reduction of the domestic primary deficit. In the structural area, program focus will be on public finance management and key sectors critical to improved growth performance. Debt relief is crucial to securing medium-term external debt sustainability and for success of the program.